2011
DOI: 10.1016/j.cageo.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Application of a neuro-fuzzy model to landslide-susceptibility mapping for shallow landslides in a tropical hilly area

Abstract: This paper presents landslide-susceptibility mapping using an adaptive neuro-fuzzy inference system (ANFIS) using a geographic information system (GIS) environment. In the first stage, landslide locations from the study area were identified by interpreting aerial photographs and supported by an extensive field survey. In the second stage, landslide-related conditioning factors such as altitude, slope angle, plan curvature, distance to drainage, distance to road, soil texture and stream power index (SPI) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 403 publications
(158 citation statements)
references
References 58 publications
4
139
0
3
Order By: Relevance
“…So, all variables in the rock-fall susceptibility map appear effective, and the prediction of the susceptibility map was measured in this way. These results are in agreement with the results of Lee and Sambath (2006), Pradhan (2006, 2007), Oh et al (2009), Jadda et al (2009), Nandi and Shakoor (2009), Oh et al (2009), Pradhan (2010, Pradhan and Lee (2010), Chauchan et al (2010) and Oh and Pradhan (2011) to apply the success rate curve and AUC to investigate the reliability of the landslides susceptibility map. We have also found that 14.…”
Section: Discussionsupporting
confidence: 81%
“…So, all variables in the rock-fall susceptibility map appear effective, and the prediction of the susceptibility map was measured in this way. These results are in agreement with the results of Lee and Sambath (2006), Pradhan (2006, 2007), Oh et al (2009), Jadda et al (2009), Nandi and Shakoor (2009), Oh et al (2009), Pradhan (2010, Pradhan and Lee (2010), Chauchan et al (2010) and Oh and Pradhan (2011) to apply the success rate curve and AUC to investigate the reliability of the landslides susceptibility map. We have also found that 14.…”
Section: Discussionsupporting
confidence: 81%
“…Based on the slope shape, the slope can be divided into three types, including concave, convex, and flat (Figure 5c). The influence of curvature on the slope erosion processes is the convergence or divergence of water during downhill flow [61]. (Figure 5b).…”
Section: Influencing Factorsmentioning
confidence: 99%
“…4 shows that 8 contours (No. 7,16,17,21,23,25,28,29) represent the areas of low or very low risk of hazard of sliding. Although the risk of landside is lessened due to the spread of low-incline slopes, the seismicity reaches up to 8 points, while rocks are of high hazard of sliding.…”
Section: Figure 5 Landscape and Environmental Risks And Hazards Causmentioning
confidence: 99%